Is there any ´Latin´ in the Latin American environmental history? New challenges for the consolidation of a regional intellectual community - Palacio, Germán (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2012)
Since the 1990s, the Latin American environmental history community has faced three principal obstacles: novelty, dispersion, and complexity. As a result of the growth in both the quantity and quality of scholarship, a critical perspective on Latin American environmental history becomes urgent. Since the nineteenth century, the Americas were subjected to a divide between ‘Latin’ and ‘Anglo’. Due to several two-way factors of transnational character that are weakening this divide, it is time to re-think critically on the meaning, utility, and explanatory potential of it. One can ask: is there any ‘Latin’ in Latin Americanenvironmental history? Consequently, both Latin American and North American environmental history scholars must take account of the porous and debilitated Latin/Anglo divide and be aware of transnationalism. This article also explores some of the ways in which the Latin American scholarship has already elaborated the global and transnational connections inherent to the study of environmental history.